Organization theory meets strategy - Stefano, Giada Di; Wezel, Filippo Carlo (Advances in strategic management ;, 2023)
Organization Theory Meets Strategy brings together researchers who work at the intersection of Organization Theory and Strategy to fuel cutting edge discussions around common questions and challenges faced by researchers working in this area. Despite approaching from differing angles and with diverse methodological approaches, the authors embrace the diversity of a dual field approach to open the conversation to a variety of Management scholars. Organization Theory Meets Strategy appeals to researchers interested in the perspective of firms with their bundles of capabilities and resources, but also with constraints and opportunities generated by social forces that are above and beyond their agency. This edited collection provides a space in which various interesting research ideas are discussed. The combination of different lenses and methods is also generative of new avenues for future research.